2014
DOI: 10.3171/2014.7.spine131059
|View full text |Cite
|
Sign up to set email alerts
|

Zero-profile hybrid fusion construct versus 2-level plate fixation to treat adjacent-level disease in the cervical spine

Abstract: Object Single-level anterior cervical discectomy and fusion (ACDF) is an established surgical treatment for cervical myelopathy. Within 10 years of undergoing ACDF, 19.2% of patients develop symptomatic adjacent-level degeneration. Performing ACDF adjacent to prior fusion requires exposure and removal of previously placed hardware, which may increase the risk of adverse outcomes. Zero-profile cervical implants combine an interbody spacer with an anterior plate into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…First, Zero-P could reduce the volume of the anterior plate, which might reduce post-operative dysphagia and simultaneously fix the cage strongly between the segments. Several published studies support this hypothesis without any significant disadvantage in clinical and radiographic results 1 6 7 8 10 14 16 17 20 21 22 25 26) . However, most of the studies compared Zero-P with the anterior plate method alone.…”
Section: Introductionmentioning
confidence: 84%
“…First, Zero-P could reduce the volume of the anterior plate, which might reduce post-operative dysphagia and simultaneously fix the cage strongly between the segments. Several published studies support this hypothesis without any significant disadvantage in clinical and radiographic results 1 6 7 8 10 14 16 17 20 21 22 25 26) . However, most of the studies compared Zero-P with the anterior plate method alone.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies have demonstrated that the development of ASD may be in uenced by the number and location of fusion segments, plate-to-disc distances, preexisting degenerative changes at adjacent segments, and excessive disc space distraction [15]. However, Zero-p interbody fusion system features Low notch, self-anchoring, and a onepiece interbody fusion device that supports and xes the segmental vertebrae [16]. It can be integrated into the intervertebral space without exceeding the anterior edge of the vertebral body, and no anterior titanium plate xation is required, which can effectively avoid the injury and stimulation of the prevertebral soft tissue and esophagus caused by the traditional titanium plate, and avoid the in uence of the traditional titanium plate on adjacent segments, thus effectively reducing the incidence of postoperative dysphagia and degeneration of adjacent segments of the cervical vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…It can be integrated into the intervertebral space without exceeding the anterior edge of the vertebral body, and no anterior titanium plate xation is required, which can effectively avoid the injury and stimulation of the prevertebral soft tissue and esophagus caused by the traditional titanium plate, and avoid the in uence of the traditional titanium plate on adjacent segments, thus effectively reducing the incidence of postoperative dysphagia and degeneration of adjacent segments of the cervical vertebra. The clinical effect of the zero-p intervertebral fusion system in the treatment of cervical degenerative diseases has been widely studied [16][17][18]. However, there are relatively fewer studies on symptomatic ASD after ACDF.…”
Section: Discussionmentioning
confidence: 99%
“…Although this surgical technique is better suited to the condition of the patient, it has disadvantages, such as increased surgical time and intraoperative blood loss, an increased rate of heterotopic ossification, the possibility of vertebral body fractures, dislocation of the implant (if not properly placed), and the possible loss of cervical lordosis. 13,[16][17][18] In addition to choosing the appropriate surgical technique for the patient's clinical and radiographical condition, other factors also influence and are considered predictors of the outcome and quality of life of the patient after the surgical procedure. The factors that predict poor prognosis of surgical outcomes can be divided into two distinct groups: those related to the patient and those related to the imaging examinations (magnetic resonance and computed tomography).…”
Section: Discussionmentioning
confidence: 99%